Quality Of Kirinyuh Leaf Liquid Organic Fertilizer and Coconut Water Waste With Pineapple Skin Bioactivator - Nitami, Arisa Putri Jihan; Asngad, Aminah (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Liquid organic fertilizer is liquid fertilizer so that plants can absorb it more easily. Liquid organic fertilizer can overcome problems arising from using inorganic fertilizers in the long term. This study aims to determine the quality of liquid organic fertilizer from kirinyuh leaves and coconut water waste by adding pineapple peel as a bioactivator. This study used the experimental method and utterly randomized design consisting of 2 factors with four combinations and three repetitions, namely factor 1 (K): a combination of the essential ingredients of kirinyuh leaves and coconut water waste (K 1: 168 ml: 82 ml & K 2: 82 ml: 168 ml). Factor II (M): Add MOL of pineapple skin (M 1: 100 ml and M 2: 150 ml). The parameters used were sensory tests regarding color, odor, pH and nitrogen, phosphorus, and potassium content. This study uses data analysis: descriptive qualitative, and quantitative. The results showed that liquid organic fertilizer has a greenish-brown color, does not have a solid fermented odor (like tape) and some have an unpleasant odor, and has a pH of 4.00 – 4.67. Based on the POC content test, only three treatments met the quality standards of SNI 19-7030-2004 for nitrogen content, namely K1M1, K1M2, and K2M1.